HIV cure research: print and online media reporting in Australia - Jennifer Power; Bianca Fileborn; Gary W. Dowsett; Jayne Lucke; Graham Brown; Jeanne Ellard; Sharon R. Lewin; Joseph D. Tucker; Sean Slavin; Jeremy Sugarman; Sophie Hill (Elsevier, 2017)
Objectives: While still in its early stages, recent scientific research towards a cure for HIV has generated widespread media interest. The aim of this paper was to explore the ways in which this research has been represented in Australian print and online media and discuss implications of this. Methods: A search of databases from four selected media outlets was conducted to identify published articles that directly discussed HIV cure research. Content analysis was used to explore the discursive framing of HIV cure research and identify the presence or absence of people living with HIV in articles. Results: In total, 95 articles were identified that had been published in print or online between 2007 and 2015. Media reports tended to focus on research breakthroughs or the future potential of HIV cure research, rather than more immediate implications of research findings. While not inaccurate, this focus often implied the field of HIV cure research was more advanced than was generally the case. There was a notable absence of commentary from people living with HIV or community advocates in media reporting. Conclusions: Media reporting may generate unrealistic expectations of HIV cure research. This raises ethical concerns that media reporting may inadvertently contribute to therapeutic or curative misconceptions among potential participants in HIV cure-related trials. To address this, scientists, HIV advocates and people living with HIV will need to work collaboratively to engage with reporters and media outlets to provide more consistent input and guidance into reporting about research towards a cure for HIV.